2007
DOI: 10.1080/00268970601181549
|View full text |Cite
|
Sign up to set email alerts
|

Rapid passage induced population transfer and coherences in the 8 micron spectrum of nitrous oxide

Abstract: Abstract:Rapid passage signals showing the effects of molecular alignment have been observed when low pressure samples of nitrous oxide are interrogated by radiation from a pulsed 7.84 µm quantum cascade laser. These effects occur when the sweep rate of the laser through a Doppler broadened absorption line is much faster than the collisional relaxation time, and when the power density of the linearly polarised laser radiation is sufficient to cause optical pumping. Using a laser pulse of duration 1.3 microseco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…It is not an electronic time constant issue, but appears to be a real swept-gain seen when the laser frequency is slewed at a sufficient rate over strongly absorbing lines with optical densities $1 and K divisible by three. Duxbury and Langford have interpreted these effects as a swept gain effect that occurs if the laser frequency is quickly slewed so that adiabatic rapid passage (ARP) can occur leading to excited state populations in select velocity sub-groups that can support coherent re-emission [38]. Their Maxwell-Bloch propagation models appear to reconcile nicely with their data taken with more intense pulsed QCLs.…”
Section: The M 4 Band Near 1217 Cm à1supporting
confidence: 56%
“…It is not an electronic time constant issue, but appears to be a real swept-gain seen when the laser frequency is slewed at a sufficient rate over strongly absorbing lines with optical densities $1 and K divisible by three. Duxbury and Langford have interpreted these effects as a swept gain effect that occurs if the laser frequency is quickly slewed so that adiabatic rapid passage (ARP) can occur leading to excited state populations in select velocity sub-groups that can support coherent re-emission [38]. Their Maxwell-Bloch propagation models appear to reconcile nicely with their data taken with more intense pulsed QCLs.…”
Section: The M 4 Band Near 1217 Cm à1supporting
confidence: 56%
“…4 The recorded time domain spectra are analogous to the optical nutation signals observed in the coherent transient experiments, and similarly the effects observed experimentally can modeled by solving the coupled Maxwell-Bloch equations. [1][2][3][4] In the previous paper, 5 on a Dicke-narrowed doublet of the 2 band of water, and in a survey paper, 6 we have shown that the time dependence of the collisional broadening may be investigated by the use of the frequency down-chirped electromagnetic radiation emitted by a long pulse duration QCL.…”
Section: Time Dependent Measurements Of Nitrous Oxide and Carbon Dioxmentioning
confidence: 97%
“…Over the past 7 years, the frequency down-chirped radiation emitted by a quantum cascade laser ͑QCL͒, used in the intrapulse 1 method, has been demonstrated to produce both saturation 2 and also molecular alignment 3 and transient gain. 4 The recorded time domain spectra are analogous to the optical nutation signals observed in the coherent transient experiments, and similarly the effects observed experimentally can modeled by solving the coupled Maxwell-Bloch equations.…”
Section: Time Dependent Measurements Of Nitrous Oxide and Carbon Dioxmentioning
confidence: 99%
See 1 more Smart Citation
“…While a theoretical description for the non-linear absorption phenomena based on optical Bloch equations exists [25,26,28], the origin of distorted line shapes in the short-pulse mode is not yet completely understood [9]. The problem is often empirically minimised by finding a compromise between a reasonable signal-to-noise ratio (SNR) and a narrow spectral width [12].…”
mentioning
confidence: 99%